2020
DOI: 10.1016/j.biopsych.2019.06.027
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Mechanisms of Opioid Addiction

Abstract: Opioid use kills tens of thousands of Americans each year, devastates families and entire communities, and cripples the healthcare system. Exposure to opioids causes long-term changes to brain regions involved in reward processing and motivation, leading vulnerable individuals to engage in pathological drug-seeking and drug-taking that can remain a lifelong struggle. The persistence of these neuroadaptations is mediated in part by epigenetic remodeling of gene expression programs in discrete brain regions. Alt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
112
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(119 citation statements)
references
References 127 publications
6
112
0
1
Order By: Relevance
“…Because of the many shared pathways across brain regions in OUD, we comprehensively mapped the extent of transcriptional overlap between the DLPFC and NAc. Such analyses may provide critical insight into the functional alterations across DLPFC-NAc circuits (3,11,(66)(67)(68)(69). To investigate overlap of alterations between regions, we used Rank-Rank Hypergeometric Overlap (RRHO) analysis (70,71).…”
Section: High Transcriptional Coherence Between Dlpfc and Nac Convergmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of the many shared pathways across brain regions in OUD, we comprehensively mapped the extent of transcriptional overlap between the DLPFC and NAc. Such analyses may provide critical insight into the functional alterations across DLPFC-NAc circuits (3,11,(66)(67)(68)(69). To investigate overlap of alterations between regions, we used Rank-Rank Hypergeometric Overlap (RRHO) analysis (70,71).…”
Section: High Transcriptional Coherence Between Dlpfc and Nac Convergmentioning
confidence: 99%
“…Further investigation into these overlapping transcripts revealed pathways enriched for factors that control the formation and degradation of the extracellular matrix (ECM) and pro-inflammatory cytokine-mediated signaling. These pathways implicate neuroinflammation as a driver of ECM remodeling and synaptic reorganization, processes which are critical for opioid-induced neuroplasticity (11).…”
Section: Introductionmentioning
confidence: 99%
“…Immediate effects of opioids result in decreased levels of consciousness, sedation (Collett 1998 ; Thompson 2000 ; Indelicato and Portenoy 2002 ), drowsiness, and sleep disturbances (Moore and Dimsdale 2002 ; Bourne and Mills 2004 ; Qureshi and Lee-Chiong 2004 ). While acute opioid exposure can impair cognition in healthy subjects (Lawlor 2002 ; Ersek et al 2004 ), enduring cognitive and psychomotor deficits occur with chronic opioid use (Sjogren et al 2000 ; Dublin et al 2015 ; Roberts et al 2018 ; Wollman et al 2019 ; Serafini et al 2020 ), including altered pain perception (opioid-induced hyperalgesia), dysregulated reward/saliency processing, hyperkatifeia, and epigenetic changes, which can persist years following abstinence (Ersche et al 2006 ; Browne et al 2020 ). The behavioral changes seen with long-term opioid use are accompanied by lasting structural and epigenetic (e.g., altered DNA methylation and expression of non-coding RNAs) alterations in brain regions implicated in mood, reward, and motivation (Upadhyay et al 2010 ; Dublin et al 2015 ; Volkow and Morales 2015 ; Koob and Volkow 2016 ; Serafini et al 2020 ).…”
Section: Overviewmentioning
confidence: 99%
“…Following the initial exposure, the addictive substance continues to have a persistent effect, and this suggests a form of cellular memory. There is strong evidence that epigenetic processes, including DNA methylation, play a key role in maintaining the long-term effects of the additive substance [16,17]. Studies particularly in model organisms have shown that drugs of abuse trigger intracellular signaling cascades that alter gene transcription, repeated exposure to the drug then results in remodeling of the epigenome that persists over time, and these epigenetic processes maintain the long-term changes in steadystate gene expression that underlie addiction [16,[18][19][20].…”
Section: Introductionmentioning
confidence: 99%